Vol 1 Maret 2023 MEMBANGUN LITERASI KEUANGAN DAN INVESTASI SYARI'AH: OPTIMALISASI PERAN LEMBAGA KEUANGAN SYARIAH DALAM MEMBANGUN EKONOMI UMAT - nur muh annuroin (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2023)
This study will discuss the description of steps that Islamic financial institutions should take to optimize their role in building the people's economy, especially in Indonesia by paying attention to whether the contract applied is in accordance with sharia rules or just hiding behind a sharia label but the practice is not in accordance with sharia rules, such as implement an interest system which in sharia interest is included in the category of usury which is haraam. This research was conducted using qualitative research methods with descriptive analysis results, Data collection was carried out by means of natural setting, primary data sources, while the data collection technique is done by participant observation, questionnaires, triangulation and in-depth interviews. Further results show that Islamic financial institutions should straighten out their roles as investment managers and as intermediary institutions between capital owners, Islamic financial institutions should minimize the bank-minded paradigm, and Islamic financial institutions should optimize mudharabah and musyarakah funding as the core business.